1 2 2

: ..

  1. #1

    Jul 2012
    5,302

    ..

    :-
    :-
    1- 5 ^3 - 45
    :-
    5 ( ^2 - 9 ) ..............
    5 ( - 3 ) ( + 3 )

    2- ( 3.7 )^2 - ( 1.3 ) ^2
    :-
    ( 3.7 )^2 - ( 1.3 )^2 = ( 3.7 - 1.3 ) ( 3.7 + 1.3 )
    ..................... = 5 2.4 = 12

    3- 2 ^2 - 2 ( + 1 )^2
    :-
    2 ^2 - 2 ( + 1 )^2 = 2 ( ^2 - ( + 1 ))^2
    = 2 ( + ( + 1 )) ( - ( + 1 ) ) = 2 ( + + 1 ) ( - - 1 )

    4- 2 ^4 + 128
    :-
    2 ( ^3 + 64 ) = 2 ( + 4 ) ( ^2 - 4 + 16 )

    :-
    :-
    1- ^2 + 5 + 6 ....................... 6 5
    :-
    ( + 2 ) ( + 3 )

    2- ^2 - 12 + 36
    :-
    ^2 - 12 + 36 ..................... 36 12
    ( - 9 ) ( - 4 )

    3- ^2 - 5 - 24
    :-
    ^2 - 5 - 24 .................... 24 5

    ( _ 8 ) ( + 3 )

    :-
    :-
    1- 2 ^2 - 13 + 15
    :-
    ( 2 - 3 ) ( - 5 ) ................... 15 2 + = - 13

    2- 24 ^3 - 56 ^2 - 10

    2 ( 12 ^2 - 28 - 5 )
    2 ( 6 + 1 ) ( 2 - 5 )

    3- 2 ^2 - 9 + 7
    :-
    ( 2 - 1 ) ( - 1 )


    :-
    1- 2 ^2 + 6 ^2 - 2
    :-
    2 ( ^2 + 3 - 1 )

    2- ^2 - 2 + ( - 2 )
    :-
    ( - 2 ) + ( - 2 )
    ( - 2 ) ( + )

    3- 7 ( 2 - 3 ) + 5 ( 2 - 3 ) + 3 ( 2 - 3 )
    :-
    ( 2 - 3 ) ( 7 + 5 + 3 )

    :-
    :-
    1- ^2 - 10 + 25 ^2
    :-
    ( ^2 - 10 + 25 ^2 )
    = ( - 5 )^2

    2- ^3 - ^2 + - 1
    :-
    = ( ^3 - ^2 ) + ( - 1 )
    = ^2 ( - 1 ) + ( - 1 ) = ( - 1 ) ( ^2 + 1 )

    3- 2 ^3 + 5 ^2 - 8 - 20
    :-
    = ( 2 ^3 - 8 ) + ( 5 - 20 )
    = 2 ( ^2 - 4 ) + 5 ( ^2 - 4 )
    = ( ^2 - 4 ) ( 2 + 5 )
    = ( + 2 ) ( - 2 ) ( 2 + 5 )











  2. #2
      Eiman
    Jul 2011
    -
    14,750

    : ..

    .......

: 1 (0 1 )